Predictors of joint damage progression and stringent remission in patients with established rheumatoid arthritis in clinical remission. (15th September 2020) - Møller-Bisgaard, Signe; Georgiadis, Stylianos; Hørslev-Petersen, Kim; Ejbjerg, Bo; Hetland, Merete Lund; Ørnbjerg, Lykke Midtbøll; Glinatsi, Daniel; Møller, Jakob; Boesen, Mikael; Stengaard-Pedersen, Kristian; Madsen, Ole Rintek; Jensen, Bente; et al.
Abstract: Objectives: To study if clinical, radiographic and MRI markers can predict MRI and radiographic damage progression and achievement of stringent remission in patients with established RA in clinical remission followed by a targeted treatment strategy. Methods: RA patients (DAS28-CRP <3.2, no swollen joints) receiving conventional synthetic DMARDs were randomized to conventional or MRI-targeted treat-to-target strategies with predefined algorithmic treatment escalations. Potentially predictive baseline variables were tested in multivariate logistic regression analyses. Results: In the 171 patients included, baseline MRI osteitis independently predicted progression in MRI erosion [odds ratio (OR) 1.13 (95% CI 1.06, 1.22)], joint space narrowing [OR 1.15 (95% CI 1.07, 1.24)] and combined damage [OR 1.23 (95% CI 1.13, 1.37)], while tenosynovitis independently predicted MRI erosion progression [OR 1.13 (95% CI 1.03, 1.25)]. A predictor of radiographic erosion progression was age, while gender predicted progression in joint space narrowing. Following an MRI treat-to-target strategy predicted stringent remission across all remission definitions: Clinical Disease Activity Index remission OR 2.94 (95% CI 1.25, 7.52), Simplified Disease Activity Index remission OR 2.50 (95% CI 1.01, 6.66), ACR/EULAR Boolean remission OR 5.47 (95% CI 2.33, 14.13). Similarly, low tender joint count and low patient visual analogue scale pain and global independently predicted achievement of more stringent remission. Conclusion: Baseline MRI osteitis and tenosynovitis were independent predictors of 2 year MRI damage progression in RA patients in clinical remission, while independent predictors of radiographic damage progression were age and gender. Following an MRI treat-to-target strategy, low scores of patient-reported outcomes and low tender joint count predicted achievement of stringent remission. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov ), NCT01656278.